Government Financial Accountability and its Implications for Economic Development - Agus Rohmat Hidayat; Ikhsan Nendi; Feri Hardianto; Difa Ameliora Pujayanti (Cakrawala Repositori IMWI)
This study examines the critical relationship between government financial accountability and economic development across developing and developed nations. Through a comprehensive analysis of financial governance mechanisms, transparency frameworks, and institutional quality, we investigate how accountability systems influence macroeconomic performance. Using panel data from 85 countries spanning 2010-2024, our empirical analysis employs fixed effects regression models and instrumental variable approaches to address endogeneity concerns. Results demonstrate that enhanced financial accountability significantly correlates with improved GDP growth rates, reduced corruption indices, and increased foreign direct investment. The study reveals that countries with robust public financial management systems, characterized by transparent budgeting processes, effective auditing mechanisms, and strong parliamentary oversight, experience 2.3% higher annual GDP growth compared to nations with weaker accountability frameworks. Furthermore, our findings indicate that the relationship between accountability and development is moderated by institutional quality, with stronger effects observed in countries with established democratic governance. The research contributes to the literature by developing a comprehensive Financial Accountability Index (FAI) and providing policy recommendations for strengthening fiscal governance in emerging economies.